2007
DOI: 10.1111/j.1468-036x.2007.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Do European Primarily Internet Banks Show Scale and Experience Efficiencies?

Abstract: "Empirical evidence shows that Internet banks worldwide have underperformed newly chartered traditional banks mainly because of their higher overhead costs. European banks have not been an exception in this regard. This paper analyses, for the first time in Europe, whether this is a temporary phenomenon and whether Internet banks may generate scale economies in excess of those available to traditional banks. Also do they (and their customers) accumulate experience with this new business model, allowing them to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 22 publications
(20 reference statements)
3
44
0
3
Order By: Relevance
“…At the same time, they had problems controlling overhead expenses. In contrast, Delgado et al (2007), who analyse a sample of European, newly established, primarily Internet banks and newly chartered traditional (clicks and mortar) banks of similar age and size, establish that Internet banks showed strong evidence of scale economies in terms of ROA and ROE. The primary source of technology-based scale effects was the Internet banks' ability to control operational expenses more efficiently than new traditional banks.…”
Section: Literature Review and Hypothesesmentioning
confidence: 95%
See 2 more Smart Citations
“…At the same time, they had problems controlling overhead expenses. In contrast, Delgado et al (2007), who analyse a sample of European, newly established, primarily Internet banks and newly chartered traditional (clicks and mortar) banks of similar age and size, establish that Internet banks showed strong evidence of scale economies in terms of ROA and ROE. The primary source of technology-based scale effects was the Internet banks' ability to control operational expenses more efficiently than new traditional banks.…”
Section: Literature Review and Hypothesesmentioning
confidence: 95%
“…The published studies can be roughly categorized into two groups. The first group of studies analyses the determinants of Internet banking adoption (Bauer & Hein, 2006;Courchane, Nickerson, & Sullivan, 2002;Hernández-Murillo, Llobet, & Fuentes, 2010;Santouridis & Kyritsi, 2014), and the second group of studies addresses the consequences of Internet banking introduction (Hitt & Frei, 2002;Delgado, Hernando, & Nieto, 2007;DeYoung, Lang, & Nolle, 2007;Ciciretti, Hasan, & Zazzara, 2009;Onay & Ozsoz, 2013). However, the existing evidence concerns mainly developed markets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the line of this, Hasan et al (2002), Nieto (2005), De Young et al (2006), Malhotra and Singh (2009) also share the same views by analyzing the banks of Italy, Spain, US and India respectively. However, Sullivan (2000) and Delgado et al (2004) envisaged the contrary results by reporting lower profitability and poorer performance for internet banks. ISSN 2377-4622 2017 Hence, performance of banks providing services through plastic cards is the untouched research issue of the banking sector.…”
Section: Review Of Literaturementioning
confidence: 89%
“…However, Furst et al (2000Furst et al ( , 2002, Sullivan (2000), De Young (2001, 2005, Hasan et al (2002), Delgado et al (2004) , Hernando and Nieto (2005) Furst et al (2000Furst et al ( , 2002, by taking the sample of US banks, found that internet banks are having better performance than non internet banks and thus outperformed non internet banks. In the line of this, Hasan et al (2002), Nieto (2005), De Young et al (2006), Malhotra and Singh (2009) also share the same views by analyzing the banks of Italy, Spain, US and India respectively.…”
Section: Review Of Literaturementioning
confidence: 99%